The assessment of drug treatment of spastic gait. Issue 11 (November 1981) - Corston, R N; Johnson, F; Godwin-Austen, R B
Abstract : The technique of polarised light goniometry was used to quantify objectively parameters of the spastic gait during a double-blind cross-over trial comparing the spasmolytic effects of DS103-282, baclofen and placebo. Only minimal objective and subjective changes in gait were found when the results of treatment with DS103-282 or baclofen were compared with those of treatment with placebo.